1. Rewrite this function...

write f(x) = (2x^3 -7)^5 as 2 simpler functions

2. Originally Posted by yess
write f(x) = (2x^3 -7)^5 as 2 simpler functions
Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB

3. You're question is kind of vague. Are you looking for something like this?

$f(x)=g(h(x))$

4. Originally Posted by CaptainBlack
Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB
yes sorry thats what i meant!

5. Originally Posted by yess
yes sorry thats what i meant!
Originally Posted by yess
write f(x) = (2x^3 -7)^5 as 2 simpler functions
Originally Posted by CaptainBlack
Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB
'

How about $h(x)=x^3$, then $g(x)=(2x-7)^5$ or maybe something simpler yet?

CB

6. Shouldn't it be:

$f(x)=g(h(x))$

Where

$g(x)=x^{5}$ and $h(x)=(2x^{3}-7)$

7. Originally Posted by downthesun01
Shouldn't it be:

$f(x)=g(h(x))$

Where

$g(x)=x^{5}$ and $h(x)=(2x^{3}-7)$
There is no unique solution.

CB